PEMBENTUKAN KOMUNITAS PERMAINAN TRADISIONAL DALAM MENINGKATKAN KECERDASAN INTERPERSONAL ANAK USIA SEKOLAH - Mareta Zawwin Ekaputra; Hidayah Nur Amalina; Vionie Augustine; Arif Budiwinarto (Diseminasi: Jurnal Pengabdian kepada Masyarakat, 2024)
The excessive use of smartphones for playing online games has a negative impact on school-age children, necessitating an alternative to divert their attention. One effective solution is introducing traditional games, which significantly benefit children's interpersonal intelligence, such as teamwork, expressing opinions, supporting each other, and decision-making. To address this issue, the team conducted a community service program in Kampung Kandungmangu, RT09/RW 03, Cisauk. This program involved 15 school-age children and included presentations, mentoring, implementation, and evaluation. The results of the program showed that participants gained a deeper understanding of traditional games and their benefits. Even after the program ended, the children continued to play traditional games to apply the knowledge and skills they acquired during the program. This indicates that traditional games not only successfully divert attention from online games but also positively contribute to the development of children's interpersonal intelligence.